Collision-free tool orientation optimization in five-axis machining of bladed disk - Chen, Li; Xu, Ke; Tang, Kai (Journal of computational design and engineering, 2015)
Bladed disk (BLISK) is a vital part in jet engines with a complicated shape which is exclusively machined on a five-axis machine and requires high accuracy of machining. Poor quality of tool orientation (e.g., false tool positioning and unsmooth tool orientation transition) during the five-axis machining may cause collision and machine vibration, which will debase the machining quality and in the worst case sabotage the BLISK. This paper presents a reference plane based algorithm to generate a set of smoothly aligned tool orientations along a tool path. The proposed method guarantees that no collision would occur anywhere along the tool path, and the overall smoothness is globally optimized. A preliminary simulation verification of the proposed algorithm is conducted on a BLISK model and the tool orientation generated is found to be stable, smooth, and well-formed.